1986
DOI: 10.1021/ja00284a003
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic reduction of carbon dioxide by nickel cyclam2+ in water: study of the factors affecting the efficiency and the selectivity of the process

Abstract: rate in the Co' neutral complexes but not in the Coo anion radicals. This argues that the isomerization mechanism is different in the two different metal oxidation states.2. The rapid isomerization of the Coo complexes may arise from lifting of symmetry restrictions to the simplest molecular isomerization mechanism in the 19-electron monoanions.3. When dibenzocyclooctatetraene is used as the ligand, the Coo monoanion has a different ground state than [CpCo(cot)]-, and CpCo(dbcot) behaves more like a cod comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
348
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(363 citation statements)
references
References 3 publications
13
348
0
2
Order By: Relevance
“…This indicates high selectivity for CO 2 reduction over the more thermodynamically favored reduction of protons to H 2 . For example, the reduction of CO 2 to CO by nickel cyclam catalysts occurs with nearly 100% current efficiency in water at pH 4.1, 163 and CO 2 is reduced to CO in 0.02 M HBF 4 in dimethylformamide solutions with current efficiencies greater than 95%. 164 In addition, some of these catalysts operate at low overpotentials so that the conversion of electrical to chemical energy is highly efficient.…”
Section: E Electrochemical Reduction Of Comentioning
confidence: 99%
“…This indicates high selectivity for CO 2 reduction over the more thermodynamically favored reduction of protons to H 2 . For example, the reduction of CO 2 to CO by nickel cyclam catalysts occurs with nearly 100% current efficiency in water at pH 4.1, 163 and CO 2 is reduced to CO in 0.02 M HBF 4 in dimethylformamide solutions with current efficiencies greater than 95%. 164 In addition, some of these catalysts operate at low overpotentials so that the conversion of electrical to chemical energy is highly efficient.…”
Section: E Electrochemical Reduction Of Comentioning
confidence: 99%
“…Although various molecular catalysts (porphyrins, corroles, cyclams, naphthyridines, and so forth) with metal centers such as Pd, Ru, Fe, Co, and Ni were investigated,31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 in the years after the discovery of Lehn's catalyst, most research has been focused on Re‐containing complexes. With an estimated average concentration of 1 ppb, Re, together with other noble metals, is one of the rarest elements in Earth's crust.…”
Section: Homogeneous Electrocatalysis For Co2 Reductionmentioning
confidence: 99%
“…Among the homogeneous electrocatalysts, Ni(II)-cyclam (cyclam: 1,4,8,11-tetrazazcyclotetradecane) and its derivatives have been known to exhibit remarkable efficiency and selectivity in converting CO 2 to CO [4][5][6][7][8][9]. It has been revealed that Ni(I)-cyclam, generated by one-electron-reduction of Ni(II)-cyclam, is the active catalytic species and the cyclam ligand stabilizes the Ni(I) state [5,7,10]. Ni(II)-cyclam, however, still exhibits rather high overpotential (ca.…”
Section: Introductionmentioning
confidence: 99%
“…-0.6 V), leading to the low energy efficiency for CO 2 conversion. In addition, Ni(II)-cyclam necessitates a mercury electrode to avoid hydrogen evolution and shows much less electrocatalytic activities on other environmentally-benign electrodes [5][6][7].…”
Section: Introductionmentioning
confidence: 99%